Profitabilitas, Tekanan Stakeholder, Komite Audit, dan Kualitas Sustainability Report - Meinawati, Kadek; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 33 No 8 (2023)DO - 10.24843/EJA.2023.v33.i08.p19, 2023)
Sustainability reports are reports issued by companies regarding performance in economic, social and environmental terms for stakeholders. Factors that influence the quality of the Sustainability report are profitability, stakeholder pressure, and the audit committee. The purpose of this study was to determine the effect of profitability, stakeholder pressure, and the audit committee on the quality of sustainability reports by using stakeholder theory and legitimacy theory. This research was conducted on banking subsector companies listed on the Indonesia Stock Exchange (BEI) during 2017-2020. The sampling technique used a purposive sampling method with a total of 44 samples obtained. The analysis technique used is multiple linear regression. The results showed that profitability, stakeholder pressure, and the audit committee had a significant positive effect on the quality of the sustainability report. Keywords: Profitability; Stakeholder Pressure; Audit Committee; Sustainability report